1982
DOI: 10.1113/jphysiol.1982.sp014410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sarcomere length, tonicity, and external sodium concentration on conduction velocity in frog muscle fibres.

Abstract: SUMMARY1. Using an optical technique, conduction velocity in isolated frog muscle fibres has been measured at different sarcomere lengths and in solutions of altered tonicity and Na content.2. Conduction velocity (in m/s) in normal Ringer solution is found to be independent of sarcomere length in the range of 2-5 Fm.3. Fibre cross-section appears to become circular with stretch to sarcomere lengths exceeding 4 hm. The data on fibre diameter and length are in agreement with the assumption that constant fibre vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Conversely, the increase in velocity across sarconiere in shortened fibers can be expected to be associated with considerably smaller (or possibly no) increase in uctuul velocity measured across a fixed distance between two recording electrodes, such as two surfaces of a SFEMG electrode. The above studies are thus not in contradiction with the results reported here; however, it should be added that the two performed on isolated single muscle fibers'&, 15 did not explore changes in velocity along contracted fibers.…”
Section: Discussioncontrasting
confidence: 50%
“…Conversely, the increase in velocity across sarconiere in shortened fibers can be expected to be associated with considerably smaller (or possibly no) increase in uctuul velocity measured across a fixed distance between two recording electrodes, such as two surfaces of a SFEMG electrode. The above studies are thus not in contradiction with the results reported here; however, it should be added that the two performed on isolated single muscle fibers'&, 15 did not explore changes in velocity along contracted fibers.…”
Section: Discussioncontrasting
confidence: 50%
“…Such a relative estimate is more appropriate also because we, in fact, estimate changes in the length of the distal portion of the muscle only. A length-independent CV is in line with the results obtained in situ by Gydikov and Kosarov [15] and by Brown et al [3], as well as with observation on amphibian muscle fibres in vitro [17,25,27] and with theoretical conclusion of Hodgkin [18]. They are, however, in contrast with the results obtained in situ by Kossev et al [20,35], for m. biceps brachii, by Morimoto [26] for m. vastus medialis, and by Arendt-Nielsen et al [2] for vastus lateralis muscle.…”
Section: Discussionsupporting
confidence: 91%
“…Amplitude, frequency characteristics and estimates of muscle fibre conduction velocity (CV) used to assess the muscleÕs functional state, are sensitive to the electrode position with respect to active muscle fibres [4,[11][12][13]18,21,23,28,33] and to changes in fibresÕ lengths [5,14,21,27,28]. A variation of the joint angle is accompanied by a change in muscle length and as a result a shift of the muscle with respect to the skin and electrodes [28].…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat larger changes may apply to the half-width of A [Ca~+], which was increased by ~20-30% at 3.8 Ixm and by ~35---45% at 4.3 p,m. However, the precise magnitude of these latter changes was more difficult to ascertain because of possible contamination, at the shorter sarcomere lengths, of the falling phase of A associated with differences in the conduction velocity of the action potential, which shows almost no variation with sarcomere length (Oetliker and Schumperli, 1982).…”
Section: Effect Of Sarcomere Length On A[ca 2+]mentioning
confidence: 99%